Preoperative Predictors for 90-Day Mortality after Pancreaticoduodenectomy in Patients with Adenocarcinoma of the Ampulla of Vater: A Single-Centre Retrospective Cohort Study - Fernandez-Placencia, R (2021)
Background: The standard treatment for ampullary adenocarcinoma is pancreaticoduodenectomy. Identification of preoperative risk factors might help the clinician to select patients fit for resection and potentially decrease morbidity and mortality after PD. We conducted a cohort study to determine the preoperative factors related to 90-day severe morbidity and mortality after PD.Methods: We conducted a retrospective cohort study in patients with a diagnosis of ampullary adenocarcinoma who underwent an open PD between January 2010 and December 2019 at our tertiary centre.Results: Independent preoperative predictors of mortality were the albumin-bilirubin (ALBI) grade 3 (OR: 21.7; CI 95: 2.1-226.9; p=0.01) and the estimated glomerular filtration rate (eGFR) <90 mL/min/1.73 m2 (OR: 17.7; CI 95: 1.8-172.6; p=0.013). The eGFR <90 mL/min/1.73 m2 (OR = 6.6; CI 95: 1.9-23.4; p=0.003) and prothrombin time (OR = 1.5; CI 95; 1.1-2.1; p=0.005) were independent predictors for severe morbidity. Conclusion: These findings suggest that baseline renal function measured by the eGFR and liver function categorized with the ALBI grading are predictors of severe morbidity and mortality. Thus, they should be considered when selecting patients for PD or the use of neoadjuvant treatments. Further research is warranted.